An Initial Characterization of Aquatic Invertebrate Community Structure in the Moose River Basin, Ontario - Bouwman, Catrien W. (1996)
The Moose River Basin in northern Ontario is an important large river system, however very little is known about its aquatic invertebrate community. As macro invertebrates are an integral part of river ecosystems, I conducted an initial assessment of the aquatic invertebrate community structure in the Moose River Basin, at both a fine, and a basin-wide, scale. The fine scale study used invertebrate data collected at five reaches within a 30km stretch of the Groundhog River. The examination of the invertebrate community at a basin-wide scale was accomplished using meta-analysis techniques on twenty-two studies conducted on various rivers within the Basin. The effect of the following factors on community structure were examined: i) the use of different sampling devices, ii) water depth, iii) substrate type, iv) sampling in two consecutive years, and v) spatial scale. I found that the use of various sampling devices resulted in significantly different estimates of community structure. This strongly suggests that consistent sampling protocols are necessary to effectively compare results within, and among, studies. The effect of water depth on community structure was inconclusive, as too few samples were collected to overcome the confounding effects of substrate type. Substrate type had a significant effect on community structure, with greater invertebrate richness and diversity found in fine substrate in the Groundhog River study, but with no consistent patterns at the basin-wide scale. Invertebrate richness and diversity did not differ significantly in the Groundhog River between two consecutive years. In both the fine-scale and the basin-wide studies, the distribution of aquatic invertebrates varied among sites within a river reach, and among reaches within a river. To further examine the biological and physical processes affecting community structure at the fine-scale, consistent sampling protocols should be employed, which may also allow basin-wide trends to emerge. Thesis Master of Science (MS)